Individualizing fetal hemoglobin augmenting therapy for β-type hemoglobinopathies patients. (July 2014) - Gravia, Aikaterini; Chondrou, Vasiliki; Sgourou, Argyro; Papantoni, Ioanna; Borg, Joseph; Katsila, Theodora; Papachatzopoulou, Adamantia; Patrinos, George P
Individual genetic composition is an important cause of variations in the response and tolerance to drug treatment. Pharmacogenomics is a modern discipline aiming to delineate individual genomic profiles and drug response. To date, there are several medical disciplines where pharmacogenomics is readily applicable, while in others its usefulness is yet to be demonstrated. Recent experimental evidence suggest that besides genomic variation within the human β-globin gene cluster, other variants in modifier genes residing outside the human β-globin gene cluster are significantly associated with response to hydroxyurea treatment in β-type hemoglobinopathies patients, deducted from the increase in fetal hemoglobin levels. This article aims to provide an update and to discuss future challenges on the application of pharmacogenomics for β-type hemoglobinopathies therapeutics in relation to the current pharmacological treatment modalities for those disorders.